PERCEPATAN PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria L.) DENGAN APLIKASI PERENDAMAN BENIH PADA MEDIA TANAM KOMPOS - NI PUTU EKA APRIASTUTI; PANDE GEDE GUNAMANTA; WAYAN LANA (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study was to determine the acceleration of the growth of Sengon Seedlings with a long treatment time of soaking the seeds planted in compost soil media. This research was conducted in the experimental garden of the Agrotechnology Study Program, Faculty of Science and Technology, Tabanan University. The study was conducted from July 2020 to October 2020, using the basic design of a factorial randomized block design (RAK) which was repeated three times. The treatment that was tried consisted of two factors, namely the immersion time factor and the compost planting media factor.The results showed that the interaction between the soaking time of Sengon seeds and the composition of the compost growing media had a very significant effect (P<0.01) on the wet weight parameters of the underground plant parts and the oven-dry weight of the underground plant parts, significantly (P < 0 0.05) on the parameters of the total wet weight of the plant and the total dry weight of the plant, while the other parameters had no significant effect (P > 0.05). The highest total oven dry weight of the plant was produced by the interaction between the composition of the growing media: soil: sand: compost (1:1:2) and the soaking time of 12 hours (K2P2), which was 2.89 g, while the lowest was produced by the interaction between the composition of the growing media. soil:sand (1:1) with no soaking (K0P0) which is 0.25 g or an increase of 1056%.